Governance of Islamic Institutions in the Society 5.0 Era: The Role of Leadership in Driving Innovation - Ridho, Muhammad; Shaieba, Halya Quzwainie (Yayasan Pendidikan Tanggui Baimbaian, 2026)
Islamic institutions face unprecedented pressures in the era of Society 5.0, where the convergence of advanced technologies with human-centered values demands a fundamental transformation of organizational governance. This conceptual study examines the pivotal role of leadership in fostering governance innovation within Islamic institutions, framed by the principles of Islamic governance (al-Maqasid asy-Syari'ah) and the imperatives of digital leadership. Through an integrative literature review drawing on empirical studies, theoretical frameworks, and contemporary discourse on Islamic management, this article argues that transformational and digital leadership serves as the primary catalyst enabling Islamic institutions to transition from conventional bureaucratic governance models toward adaptive, evidence-based, and transparent governance structures. The findings reveal three intersecting dimensions: (1) Society 5.0 compels Islamic institutions to integrate physical and virtual spaces through technology while preserving Islamic values; (2) Islamic governance, rooted in principles of shura (consultation), 'adl (justice), amanah (trust), and siddiq (integrity), provides an ethical corrective to secular governance models; and (3) transformational leadership bridges technological potential with organizational competencies, creating sustainable value aligned with Maqasid asy-Syari'ah. This study contributes a synthesized framework for Islamic institutional leaders navigating the tensions between technological disruption and spiritual identity, offering practical implications for governance reform in Islamic educational and philanthropic organizations.